2015
DOI: 10.1590/s0036-46652015000600009
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas spp. ISOLATED FROM THE ORAL CAVITY OF HEALTHCARE WORKERS FROM AN ONCOLOGY HOSPITAL IN MIDWESTERN BRAZIL

Abstract: This cross-sectional study, performed in an oncology hospital in Goiania, aimed to characterize the prevalence of oral colonization and antimicrobial susceptibility of Pseudomonas spp. isolated from the saliva of healthcare workers. Microorganisms were subjected to biochemical tests, susceptibility profile, and phenotypic detection. Of 76 participants colonized with Gram negative bacilli, 12 (15.8%) harbored Pseudomonas spp. Of all isolates, P. aeruginosa (75.0%), P. stutzeri (16.7%), and P. fluorescens (8.3%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…The role of Bacillus acidophilus as a cariogenic agent was reported earlier this century [32,33]. Early studies reported diverse microorganisms as cariogenic agents like Streptococcus mutans [34][35][36], S. sanguinis, Bacillus cereus [37], L. acidophilus [38], S. aureus [39][40][41][42], S. sobrinus [43,44], Pseudomonas stutzeri [45], S. haemolyticus [46]. L. rhamnosus, and L. salivarus found in the current study, which belongs to the casei group of Lactobacillus [47].…”
Section: Discussionsupporting
confidence: 77%
“…The role of Bacillus acidophilus as a cariogenic agent was reported earlier this century [32,33]. Early studies reported diverse microorganisms as cariogenic agents like Streptococcus mutans [34][35][36], S. sanguinis, Bacillus cereus [37], L. acidophilus [38], S. aureus [39][40][41][42], S. sobrinus [43,44], Pseudomonas stutzeri [45], S. haemolyticus [46]. L. rhamnosus, and L. salivarus found in the current study, which belongs to the casei group of Lactobacillus [47].…”
Section: Discussionsupporting
confidence: 77%
“…On the other hand, P. fluorescens , E. coli , and A. haemolyticus also appeared more frequently than other isolated Gram-negative species. P. fluorescens, which is nonpathogenic, is mainly identified at low levels in the microflora of the human body, and it accounts for 8.3% of Gram-negative bacteria found in oral flora [29]. The prevalence of E. coli and A. haemolyticus in the oral cavity was also estimated and identified as associated with dental caries and periodontitis [25].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Pseudomonas spp. was isolated from the saliva of 15% of all healthcare workers from an oncology hospital in Mid-western Brazil 8. Occupational exposure in healthcare workers also may be considered as a risk factor of bacterial colonisation 9…”
Section: Discussionmentioning
confidence: 99%